Forever - Stiefvater, Maggie, 1981- (New York : Scholastic Press, 2011)
A human girl and her werewolf boyfriend must fight for their love as death comes closing in.
Keywords: Romance fiction; Wolves -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Metamorphosis -- Juvenile fiction; Supernatural -- Juvenile fiction; Love -- Fiction; Wolves -- Fiction; Human-animal relationships -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction; Young adult fiction